2018
DOI: 10.1002/path.5048
|View full text |Cite
|
Sign up to set email alerts
|

The value of cell‐free DNA for molecular pathology

Abstract: Over the past decade, advances in molecular biology and genomics techniques have revolutionized the diagnosis and treatment of cancer. The technological advances in tissue profiling have also been applied to the study of cell-free nucleic acids, an area of increasing interest for molecular pathology. Cell-free nucleic acids are released from tumour cells into the surrounding body fluids and can be assayed non-invasively. The repertoire of genomic alterations in circulating tumour DNA (ctDNA) is reflective of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 192 publications
(236 reference statements)
1
71
0
Order By: Relevance
“…Previous studies suggested that cfDNA could activate PRRs . However, aberrational activation of PRRs could induce an imbalance in the inflammation‐immune network, contributing to sepsis, septic shock, or even death.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that cfDNA could activate PRRs . However, aberrational activation of PRRs could induce an imbalance in the inflammation‐immune network, contributing to sepsis, septic shock, or even death.…”
Section: Introductionmentioning
confidence: 99%
“…Most cfDNA fragments are of 180-200 bp in length, and their levels in the serum are relatively low because of their rapid clearance by the spleen, liver, and kidneys. 2,11,16 This makes it challenging to study cfDNA by gel electrophoresis. Therefore, it is necessary to concentrate cfDNA before conducting any studies.…”
Section: Concentration Of Dna In the Dna-gelmentioning
confidence: 99%
“…15 A high isolation efficiency is vital for a successful cfDNA analysis, particularly in early cancers, as the level of cfDNA has been reported to be correlated with the cancer burden. 16,17 Similarly, the fragment size, which is dependent on the cellular release mechanisms, should be considered while analyzing the serum cfDNA. 2,18 Detection of the specic DNA changes, such as in MYCN sequences, MSI, and LOH in cfDNA, associated with cancer has been reported to be an effective method for cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating cell-free DNA (cfDNA) is degraded small DNA fragments found circulating freely in the bloodstream (plasma and serum) and other body fluids. It is mostly double-stranded extracellular molecules of DNA with smaller fragments around 70 bp to 200 bp which do not necessarily originate from the tumor [11,12]. Based on earlier studies, researchers found that the presence of cfDNA is significantly higher in cancer patients compared to healthy patients.…”
Section: Introductionmentioning
confidence: 99%